Food insecurity is associated with mental health problems among Canadian youth. Issue 8 (12th February 2021) - Men, Fei; Elgar, Frank J.; Tarasuk, Valerie
Abstract : Background: Research has linked food insecurity to mental health problems, though little is known about this relationship among Canadian youth. We investigate the association between food insecurity severity and mental illnesses in a nationally representative youth sample. Methods: We sampled 55 700 youth 12–24 years from recent cycles of Canadian Community Health Survey. Household food insecurity was measured using a standard 18-item questionnaire. We fitted Poisson regressions on self-rated mental health and diagnosed mood and anxiety disorders, controlling for sociodemographic confounders. Clinical assessments of emotional distress, major depression and suicidal ideation were examined in subsamples with available data. We stratified the sample by gender, age and survey cycle to test potential demographic heterogeneity. Results: One in seven youth lived in marginal (5.30%), moderate (8.08%) or severe (1.44%) food insecurity. Results showed that food insecurity was associated with higher likelihood of every mental health problem examined. The association was graded, with more severe food insecurity linked to progressively worse mental health. Notably, marginal, moderate and severe food insecurity were associated with 1.77, 2.44 and 6.49 times higher risk of suicidal thoughts, respectively. The corresponding relative risk for mood disorders were 1.57, 2.00 and 2.89; those for anxiety disorders were 1.41, 1.65 and 2.58. Moderate food insecurity was more closely associated with mental health problems in 18–24 year olds than in 12–17 year olds. Conclusions: Food insecurity severity was associated with poorer mental health among Canadian youth independent of household income and other socioeconomic differences. Targeted policy intervention alleviating food insecurity may improve youth mental health.